Car-4-U: Web based car purchasing search system / Deepak Sharma Terlok Chand - Deepak Sharma , Terlok Chand (2001)
This report is about a web based car purchasing search system Car - 4 - U. Car - 4 - U consists of three main modules which are the administrator module, the dealer module and the public user module. The administrator module is for the developer to maintain the system, hence a user name and password will be needed to log in. A developer will be able to add new data regarding cars, delete any unwanted or purchased cars, update existing data, change password and view the feedback entered by users in the administrator module. The dealer module is for the car dealers to be able to input the data of the vehicles for sale, update data of any cars up for sale, or even to remove the vehicles that are already sold. The third module, the public user module, is for users in general. Users are able to search by entering a keyword into the form and the page will display the results. Car - 4 - U does not carry out sale or purchasing of cars via the web, but only acts as the middleman between the interested buyers and the respective car dealers. There are also added features in Car- 4- U. One of them is the random search. By just clicking on the random button, data of a randomly chosen car will be displayed. Another feature is the feedback page. Users are able to evaluate the system or provide any suggestions, which will help the administrator in maintaining and further improving the website. The main reason for choosing the Internet approach is because of the popularity and benefits of a web application. It is definitely faster and easier to search for your car via the web rather than to drive around the whole country looking for your dream car. Abstract Besides that, with tools like Microsoft FrontPage98, an attractive web application can be created. Furthermore, with its administrator module as part of the system, a developer can easily enhance the performance of the system from time to time. Finally, Car - 4 - U is expected to help users in accommodating to the users time schedule and convenience in searching for the perfect vehicle.